2019
DOI: 10.11648/j.avs.20190706.12
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Distribution and Status of the Snow Leopard Population (<i>Panthera uncia</i>) in Western Mongolia

Abstract: Studies of the distribution, assessment of the Snow leopard population, as well as the state of the populations of its main prey species, the impact of anthropogenic factors are the basis for the development of long-term and effective action plans and strategies for its conservation. To this end, we have carried out work on three different territories of the Mongolian Altai: Jargalant, Bumbat and Baatar Khairkhan Mountains. All three territories differ in the nature of the location in relation to other parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
2
8
0
Order By: Relevance
“…We observed a correlation between population density and marking activity: as the population density increased, the marking activity increased as well. The same results were recorded in the Jargalant Mountains in Mongolia (Lukarevskiy et al, 2019). In the Bashkel section of the Sarychat-Ertash Reserve, the marking activity was 10-12 scrapes/km, while in the Solomo-Sary-Echki section it was from 23 to 33 scrapes/km.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…We observed a correlation between population density and marking activity: as the population density increased, the marking activity increased as well. The same results were recorded in the Jargalant Mountains in Mongolia (Lukarevskiy et al, 2019). In the Bashkel section of the Sarychat-Ertash Reserve, the marking activity was 10-12 scrapes/km, while in the Solomo-Sary-Echki section it was from 23 to 33 scrapes/km.…”
Section: Resultssupporting
confidence: 80%
“…Determination of the age of traces of vital activity was necessary to estimate the frequency of visits to a certain site by snow leopards, as well as the freshness of excrement. As in other areas, such as Mongolia, the intensity of marking increases from the periphery to the center of the group's range (Lukarevskiy and Purevsuren, 2011;Lukarevskiy et al, 2019). Our field observations in the Sayano-Shushensky Reserve, and on some ranges in the Tien Shan showed that the snow leopard marks the territory only if there is a female present.…”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations